Respondents' area of preference when disaster strikes: a case study of Cameron Highland - Rabe, Noor Suzilawati; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zen, Ismawi; Sabri Muda, Rahsidi; Mamat, Ahmad Fadhli (Malaysian Institute Of Planners, 2019)
Disaster can be understood as the probability or threat of quantifiable damage, injury, liability, loss, or any other negative occurrence that is caused by external or internal vulnerabilities that required an immediate action. Therefore, this study intends to understand respondents’ preferences of location when disaster strikes their settlements/ villages. Their responses are important to indicate their preparedness when facing disaster. Data collection was employed using the questionnaire survey method to the 11 villages. The selection of population was based on a cluster random sampling to ensure equal probability chances were given to every individual in every village. A total of 847 responses were able to be used for data analysis. The results show that the respondents’ knowledge on safe location was influenced by their demographic background. In addition, their experience with disasters and residential area also influenced their area of preference to seek refuge in the event of a disaster. Thus, an active promotion of such information related to risk management and reduction should be varied to cater the unique characteristics of the population.